Membangun Budaya Kolaborasi Digital Melalui Fandom: Kasus Indonesian Dears with Love - Nuril Hidayah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. In the recent years, fandom has gained its own place in the study of cultural changes that occur as a result of digital transformation. On the one hand, psychological features underlining fandom relation have become the motor that drives acceleration of digital skill adaptation. On the other hand, digital transformation also encourages changes in the fandom from old pattern of relationships that are dyadic to triadic. For fandom of international figures, this triadic relationship pattern has resulted in various digital collaboration initiatives at international and local levels. In the context of Indonesia, which is currently promoting a digital culture that is Indonesian-ish in nature, it will be very interesting to see how international fandom localizes its triadic digital collaboration culture. Indonesian Dears with Love is a very interesting case because it clearly states its vision of joining cultural diplomacy. This study seeks to reveal various aspects of digital fandom collaboration using a qualitative virtual ethnographic approach. The data is gathered using various ways ranging from participatory observation, FGD, email correspondence, and autoetnography. The study found that that the culture of digital participation and collaboration in the fandom community plays a major role in motivating members to improve their digital skills. This study also shows that effective digital participation and collaboration in the fandom community can be carried out due to the canon and its values ​​as a social binder, human resources with appropriate capacities and interests, as well as the existence of shared values ​​that guide the process of interaction and communication in the collaboration. Abstrak. Dalam beberapa tahun terakhir, fandom telah mendapatkan tempat tersendiri dalam studi tentang perubahan budaya yang terjadi sebagai akibat dari transformasi digital. Di satu sisi, fitur psikologis yang menggarisbawahi hubungan fandom telah menjadi motor yang mendorong percepatan adaptasi keterampilan digital. Di sisi lain, transformasi digital juga mendorong perubahan fandom dari pola hubungan lama yang dyadic menjadi triadic. Bagi fandom tokoh internasional, pola hubungan triadik ini telah melahirkan berbagai inisiatif kolaborasi digital di tingkat internasional dan lokal. Dalam konteks Indonesia yang saat ini sedang menggalakkan budaya digital yang bersifat keindonesiaan, akan sangat menarik untuk melihat bagaimana fandom internasional melokalisasi budaya kolaborasi digital triadiknya. Indonesian Dears with Love merupakan kasus yang sangat menarik karena dengan jelas menyatakan visinya untuk bergabung dengan diplomasi budaya. Penelitian ini berusaha mengungkap berbagai aspek kolaborasi fandom digital menggunakan pendekatan etnografi virtual kualitatif. Pengumpulan data dilakukan dengan berbagai cara mulai dari observasi partisipatif, FGD, korespondensi email, dan autoetnografi. Studi ini menemukan bahwa budaya partisipasi dan kolaborasi digital dalam komunitas fandom memainkan peran utama dalam memotivasi anggota untuk meningkatkan keterampilan digital mereka. Kajian ini juga menunjukkan bahwa partisipasi dan kolaborasi digital yang efektif dalam komunitas fandom dapat dilakukan karena kanon dan nilai-nilainya sebagai pengikat sosial, sumber daya manusia dengan kapasitas dan minat yang sesuai, serta adanya nilai-nilai bersama. yang memandu proses interaksi dan komunikasi dalam kolaborasi.